2022
DOI: 10.1002/viw.20200118
|View full text |Cite
|
Sign up to set email alerts
|

Using all our genomes: Blood‐based liquid biopsies for the early detection of cancer

Abstract: The pursuit of highly sensitive and specific cancer diagnostics based on cell‐free nucleic acids isolated from minimally invasive liquid biopsies has been an area of intense research and commercial effort for at least two decades. Most of these tests detect cancer‐specific mutations or epigenetic modifications on circulating DNA derived from tumor cells (ctDNA). Although recent FDA approvals of both single and multianalyte liquid biopsy companion diagnostic assays are proof of the tremendous progress made in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 104 publications
(81 reference statements)
0
19
0
Order By: Relevance
“…[ 15 ] Under the protection of a phospholipid bilayer membrane, [ 16 ] exosomes derived from tumor cells can be detected stably in a variety of body fluids, reflecting the real‐time tumor loading status, and were considered promising tools for liquid biopsy. [ 17,18 ] It is reported that Glypican 1‐positive exosomes can accurately distinguish early pancreatic cancer from benign pancreatic diseases, with a diagnostic sensitivity and specificity reaching 100%; these findings opened a new avenue in the application of exosomes for the early diagnosis of tumors. [ 19,20 ] Simultaneously, the commonly used exosome isolation and detection methods, such as ultracentrifugation and western blot, still rely on large and expensive equipment and are time‐consuming.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Under the protection of a phospholipid bilayer membrane, [ 16 ] exosomes derived from tumor cells can be detected stably in a variety of body fluids, reflecting the real‐time tumor loading status, and were considered promising tools for liquid biopsy. [ 17,18 ] It is reported that Glypican 1‐positive exosomes can accurately distinguish early pancreatic cancer from benign pancreatic diseases, with a diagnostic sensitivity and specificity reaching 100%; these findings opened a new avenue in the application of exosomes for the early diagnosis of tumors. [ 19,20 ] Simultaneously, the commonly used exosome isolation and detection methods, such as ultracentrifugation and western blot, still rely on large and expensive equipment and are time‐consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid biopsy not only plays an important role in tumor diagnosis but also in assessing tumor prognosis, monitoring treatment efficacy and resistance, and treatment selection. 26 Additionally, there are many commercial kits that are currently in use. 26 Metabolic reprogramming is considered one of the hallmarks of cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Additionally, there are many commercial kits that are currently in use. 26 Metabolic reprogramming is considered one of the hallmarks of cancer. 7 In recent years, metabolic fingerprints have been used as early diagnostic markers of tumors, including for lung adenocarcinoma, 27 colorectal cancer, 28 breast cancer, 29 and early-stage gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, CTCs show limited sensitivity of 70% and require hours for antibody recognition and enrichment, making it infeasible for large‐scale cancer screening. [ 6 ] At the molecular level, omics tools, including genomics, [ 7 ] proteomics, [ 8 ] and metabolomics, [ 9 ] inform clinical decision‐making for cancer diagnosis and guide precision medicine. Notably, metabolic analysis, which is closer to disease phenotypes, measures the end products of biological activities and represents a promising tool for the detection of early‐stage cancer.…”
Section: Introductionmentioning
confidence: 99%